2008
DOI: 10.1093/brain/awn247
|View full text |Cite
|
Sign up to set email alerts
|

Structural dissociation of attentional control and memory in adults with and without mild traumatic brain injury

Abstract: Memory and attentional control impairments are the two most common forms of dysfunction following mild traumatic brain injury (TBI) and lead to significant morbidity in patients, yet these functions are thought to be supported by different brain networks. This 3 T magnetic resonance diffusion tensor imaging (DTI) study investigates whether microstructural integrity of white matter, as measured by fractional anisotropy (FA) within a small set of individually localized regions of interest (ROIs), is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
228
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(253 citation statements)
references
References 55 publications
20
228
3
2
Order By: Relevance
“…In their study, they found that the number of structures with reduced FA correlated with executive, attentional, and memory cognitive measures. A number of other studies show that WM tract damage may be able to account for some forms of cognitive dysfunction (30,36). In summary, DTI can detect microstructural WM injury early after TBI, and there is a correlation with reduced FA, the number of affected tracts, and cognitive deficits even in mTBI.…”
Section: Conventional Mri Techniquesmentioning
confidence: 80%
“…In their study, they found that the number of structures with reduced FA correlated with executive, attentional, and memory cognitive measures. A number of other studies show that WM tract damage may be able to account for some forms of cognitive dysfunction (30,36). In summary, DTI can detect microstructural WM injury early after TBI, and there is a correlation with reduced FA, the number of affected tracts, and cognitive deficits even in mTBI.…”
Section: Conventional Mri Techniquesmentioning
confidence: 80%
“…Findings suggest that the effects of mTBI are indeed widespread, consistent with the distribution of DTI abnormalities observed during the chronic phase following mTBI. [4][5][6]34 Given that the participants were all scanned within 6 days of injury, it is plausible that some of these acute abnormalities may evolve into more chronic WM changes. Longitudinal DTI investigation of patients with mTBI is underway to evaluate this further.…”
Section: Discussionmentioning
confidence: 99%
“…Other research, involving patients with a GCS 13-15, using a broad range of analyses, including TBSS, have reported abnormal diffusion measures in a subset of regions covered by the significant RD cluster reported in the current study. Specifically, such regions were observed in the IC, 24,26,29,32,[53][54][55][56][57][58] in either the inferior frontooccipital and/or inferior long fasciculus 27,28,[59][60][61] and the anterior thalamic radiation. 60 The current study lends further support to an earlier hypothesis, 12 which suggested that the prevalence of crossing and merging WM fiber tracts in the anatomical region of the RD cluster might make this particular area more vulnerable to the type of forces acting on the brain during the course of a concussion.…”
Section: Longitudinal Dti Study Of Wm Tracts After Srcmentioning
confidence: 99%
“…Further, significant correlations between attentional control and FA were found within the left anterior corona radiata as well as memory performance and FA within the UF. 28 A DTI study on patients with mTBI 29 demonstrated increased FA and decreased RD in the subacute phase after injury and subsequent partial normalization of FA values in left corona radiata and splenium. These studies provide evidence that anisotropy measurements cannot only be used to assess alterations in the microstructure of the WM, but also provide a biomarker of cognitive function and dysfunction.…”
Section: Introductionmentioning
confidence: 99%